Lesson study as a trigger for preservice physics and chemistry teachers’ learning about inquiry tasks and classroom communication - Conceição, Teresa (2022)
Purpose – The purpose of this paper is to understand what physics and chemistry preservice teachers learn on the nature of the inquiry tasks and about classroom communication in an inquiry task when they take part in a lesson study. Design/methodology/approach – This is a qualitative and interpretive research which was carried out within a master’s degree course in physics and chemistry teaching with three preservice teachers. Data were collected from participant observation with video recording, interviews, written reflections and group report by the preservice teachers. This two-cycle lesson study was conducted over 12 sessions. The data analysis took place through asking questions and using the constant comparison method, which allowed the identification of the most relevant issues about the preservice teachers learning according to the categories nature of the inquiry tasks and communication promoted by the teacher. Findings – The results show that the preservice teachers learnt to identify the characteristics of inquiry tasks, how to develop an inquiry task when planning the research lesson and acknowledged its potential for student learning. Moreover, the preservice teachers acknowledged the fact that the classroom communication promoted by the teacher fostered student participation, negotiation of meanings about scientific concepts and construction of new learning that can be shared within the class. Research limitations/implications – Research is needed as regards how initial teacher education providers may contribute to the learning of preservice teachers in lesson study in initial teacher education programmes. Originality/value – This research contributes to show potentialities of lesson study in the initial teacher education of preservice physics and chemistry teachers.